"Make Me Feel at Ease and at Home": Differential Care Preferences of Nursing Home Residents. (15th April 2015) - Bangerter, Lauren R.; Van Haitsma, Kimberly; Heid, Allison R.; Abbott, Katherine
Abstract: Purpose of the Study: Assessing and honoring older adults' preferences is a fundamental step in providing person-centered care in long-term care facilities. Researchers and practitioners have begun to develop measures to assess nursing home (NH) residents' everyday preferences. However, little is known about how residents interpret and conceptualize their preferences and what specific clinical response may be needed to balance health and safety concerns with preferences. Design and Methods: We used content analysis to examine interview responses on a subset of eight open-ended items from the Preferences of Every-day Living Inventory for Nursing Home (PELI-NH) residents with 337 NH residents (mean age 81). We considered how residents self-define various preferences of care and the associated importance of these preferences. Results: Residents identified preferences for interpersonal interactions (greetings, staff showing care, and staff showing respect), coping strategies, personal care (bathroom needs, setting up bedding), and healthcare discussions. Respondents highlighted specific qualities and characteristics about care interactions that are necessary to fully meeting their everyday preferences. Implications: Results contribute to an emergent body of research that utilizes patient preferences to achieve the goals of person-centered care. The complexity of these responses substantiates the use of qualitative inquiry to thoroughly assess and integrate NH resident preferences into the delivery of person-centered care.